Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1080/10790268.2006.11753857
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Peripheral Adenosine A2 Receptors in Adenosine A1 Receptor-Mediated Recovery of Respiratory Motor Function After Upper Cervical Spinal Cord Hemisection

Abstract: Background/Objective: In an animal model of spinal cord injury, a latent respiratory motor pathway can be pharmacologically activated through central adenosine A 1 receptor antagonism to restore respiratory function after cervical (C2) spinal cord hemisection that paralyzes the hemidiaphragm ipsilateral to injury. Although respiration is modulated by central and peripheral mechanisms, putative involvement of peripheral adenosine A 2 receptors in functional recovery in our model is untested. The objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…The authors suggested that while spinal mechanisms are involved in mediating long term facilitation, putative involvement of adenosine receptors in the carotid body may also be involved (Golder et al, 2008). The assertion is in agreement with previous findings from our lab (Bae et al, 2005; James and Nantwi, 2006). In our lab we observed that systemic administration (0.5-2.0 mg/kg, i.v.)…”
Section: Mechanism(s) Of Actionssupporting
confidence: 94%
“…The authors suggested that while spinal mechanisms are involved in mediating long term facilitation, putative involvement of adenosine receptors in the carotid body may also be involved (Golder et al, 2008). The assertion is in agreement with previous findings from our lab (Bae et al, 2005; James and Nantwi, 2006). In our lab we observed that systemic administration (0.5-2.0 mg/kg, i.v.)…”
Section: Mechanism(s) Of Actionssupporting
confidence: 94%
“…Followup experiments indicated that theophylline acted primarily through the adenosine-A 1 receptor (60), but the magnitude of the recovery could be further enhanced by targeting both A1 and A2 receptors. Specifically, studies that simultaneously targeted central A1 receptors (DPCPX, a specific A1-receptor antagonist) and peripheral A2 receptor CGS-21680 (a peripherally specific A2-receptor agonist) enhanced the magnitude of recovered function over that attained by A1-receptor blockade alone (61,62).…”
Section: Activation Of the Crossed Phrenic Pathwaymentioning
confidence: 99%
“…Although central antagonism of adenosine A 1 receptors mediates functional recovery, it has also been demonstrated that although adenosine A 2A receptors do not appear to mediate recovery after injury, activation of peripherally located adenosine A 2A receptors by specific agonists can enhance and/or subserve the centrally mediated adenosine A 1 receptor effect (14,15). Recently, by using immunohistochemistry and in-situ hybridization, we demonstrated a positive colocalization of adenosine A 1 receptor mRNA and immunoreactivity (protein) within the phrenic motoneurons of the ventral horns of the cervical spinal cord (16).…”
Section: Introductionmentioning
confidence: 99%